Strategi Integrasi Metode Qawa’id wa Tarjamah Berbasis Platform Lumi Education dalam Pembelajaran Maharah Qira’ah - Mar'a Aqila Sholiha; Tulus Musthofa (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2026)
Learning maharah qira’ah at the MTs level still faces various challenges, particularly students’ low ability to comprehend Arabic texts comprehensively despite having studied Nahwu and Sharaf rules. On the other hand, the Qawa’id wa Tarjamah method remains relevant because it helps students understand texts through grammatical analysis and translation activities, however, its implementation is often considered monotonous and less compatible with the characteristics of learners in the digital era. This study aims to formulate an integration strategy of the Qawa’id wa Tarjamah method based on the Lumi Education platform in teaching maharah qira’ah at the MTs level. The study employed a qualitative approach with a literature study design. Data were collected from scientific journal articles, books, and various literature relevant to the research topic. Data analysis was conducted using content analysis techniques through the stages of data condensation, data display, and conclusion drawing. The analysis suggests that the integration strategy can be implemented through the utilization of interactive book and interactive quiz features that accommodate reading activities, grammatical analysis, translation, and gradual text comprehension. This integration is necessary because it preserves the strength of the classical method while providing a more interactive, flexible, and student-centered learning experience. This study contributes conceptually to the development of digital-based Arabic learning and serves as practical reference for teachers in designing maharah qira’ah instruction that is more adaptive to the needs of twenty-first century learning.